Veno-Arterial Extracorporeal Membrane Oxygenation in Cardiotoxic Drug-Induced Cardiogenic Shock: A Systematic Narrative Review - Debora Emanuela Torre; Domenico Mangino; Carmelo Pirri (Life, 2025)
Background: Severe poisoning can lead to catastrophic cardiovascular collapse, often progressing to multiorgan failure and death. While intensive supportive care and pharmacological intervention remain the cornerstone of management, cases of refractory cardiogenic shock, particularly those caused by membrane stabilizing agents and calcium channel blockers, pose a significant therapeutic challenge. Extracorporeal membrane oxygenation (ECMO) has emerged as a potential life-saving intervention in critically ill patients. This review examines the feasibility, clinical outcomes, and optimal indications for ECMO in the management of drug-induced cardiogenic shock. Methods: A systematic narrative review was conducted to evaluate the current evidence of ECMO use in poisoning-related cardiovascular failure, with a particular focus on patient selection criteria and the prognostic determinants of therapeutic resistance. Results: Extracorporeal membrane oxygenation may serve as a crucial hemodynamic support strategy in drug-induced circulatory collapse. Most reported cases involve peripheral ECMO, demonstrating variable but promising survival outcomes. Conclusions: Despite its potential to rescue patients from otherwise fatal toxic cardiomyopathy, the role of ECMO remains incompletely defined. Further prospective studies are essential to refine patient selection criteria and identify the toxicant-specific predictors of therapeutic failure. A deeper understanding of these factors may enhance clinical decision making and improve survival rates in severe poisoning cases.